Association between fragmented QRS and postprocedural rhythm disturbances in patients who underwent transcatheter aortic valve implantation - Duran,Mustafa (2021)
SUMMARY INTRODUCTION: According to recent studies, the rate of atrioventricular block requiring permanent pacing in patients following transcatheter aortic valve implantation varied between 5.7% and 42.5%. Fragmented QRS is a useful marker of myocardial scar and can predict adverse cardiac events. In this study, we examined association between f ragmented QRS and postprocedural rhythm disturbances and the need for permanent pacing in patients who underwent transcatheter aortic valve implantation. OBJECTIVE: In this study, we examined association between fragmented QRS and postprocedural rhythm disturbances and the need for permanent pacing in patients who underwent transcatheter aortic valve implantation’ sentence is enough for it. METHODS: We retrospectively analyzed standard 12-lead electrocardiographic recordings of 124 consecutive patients in whom a CoreValve prosthesis was implanted. We examined 12-lead electrocardiogram before and after procedure along with one- and six-month follow-up. We documented QRS fragmentation and postprocedural rhythm disturbances. RESULTS: There was a significant increase in the frequency of left bundle branch block, (21.1 versus 0%, p<0.05) and the incidence of atrioventricular blocks requiring permanent pacing (21.1 versus 0%, p<0.05) following transcatheter aortic valve implantation in patients whose preprocedural electrocardiogram recordings revealed fragmented QRS compared to those without fragmented QRS. Based our collected data, the presence of QRS fragmentation in anterior derivations was the only independent factor associated with postprocedural rhythm disturbances (B-value 0.217; OR 0.805; 95%CI 0.136–4.78; p=0.004). CONCLUSION: Our data showed an increased risk for the development of new-onset left bundle branch block and atrioventricular blocks following transcatheter aortic valve implantation in patients whose baseline electrocardiogram recordings demonstrated QRS fragmentation.